2011
DOI: 10.1097/olq.0b013e31820ead73
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to HIV Testing Among HIV/AIDS Concurrently Diagnosed Persons in New York City

Abstract: A lack of perception of risk was the most common reason for not testing for HIV sooner among these concurrently diagnosed patients. The majority of these patients were accessing medical care, indicating that this population could have benefited from routine HIV testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 30 publications
0
14
0
1
Order By: Relevance
“…In fact, when HIV-infected patients were asked why they had not been tested earlier for HIV, the most common answer (69%) was that they did not feel that they were at risk for HIV infection. 43 Patients also expressed concerns about the confidentiality, access, and anonymity of HIV testing in a health care setting. Furthermore, a recent survey of patients in a health care setting demonstrated that most were unaware that 20% of people infected with HIV in the United States are unaware of their diagnosis and that the CDC recommends HIV screening without regard to risk, and they assumed that consent for HIV testing would be overwhelming or intimidating.…”
Section: Public Awareness and Perceptionmentioning
confidence: 99%
“…In fact, when HIV-infected patients were asked why they had not been tested earlier for HIV, the most common answer (69%) was that they did not feel that they were at risk for HIV infection. 43 Patients also expressed concerns about the confidentiality, access, and anonymity of HIV testing in a health care setting. Furthermore, a recent survey of patients in a health care setting demonstrated that most were unaware that 20% of people infected with HIV in the United States are unaware of their diagnosis and that the CDC recommends HIV screening without regard to risk, and they assumed that consent for HIV testing would be overwhelming or intimidating.…”
Section: Public Awareness and Perceptionmentioning
confidence: 99%
“…Research has identified a variety of health-care related barriers to testing, including limited access, lack of knowledge of rights and services, actual or expected costs, and perceived clinic-based impediments (Beattie et al, 2012; Deblonde et al, 2010; Flowers, Knussen, Li, & McDaid, 2013; Huang et al, 2012; Mills et al, 2011; Mimiaga et al, 2009; Prestage, Brown, & Keen, 2012; Schwarcz et al, 2011). Demographic circumstances, such as education and income, have also often been linked to HIV testing (Holt et al, 2011; Li et al, 2012; Mimiaga et al, 2009), including in Colombia (Galindo et al, 2011).…”
mentioning
confidence: 99%
“…15,16 Barriers to HIV testing fall within several well-described categories: individual level concerns including fear of results, internal and external stigma attached to testing, anxiety waiting for results, lack of recognition of risk status, and low HIV knowledge; provider level barriers such as lack of funding, limited awareness of testing guidelines, and discomfort; and system related barriers such as limited availability of rapid testing. [17][18][19][20] Although data regarding black non-U.S.-born individuals and HIV testing is limited, data from Europe indicate that black immigrants (primarily from sub-Saharan Africa) experience many of the same barriers as native born individuals, including fear of positive test results and its related personal and social consequences, lack of preventive health behavior, and denial of HIV risk. HIVrelated stigma, language barriers, and low HIV knowledge are also common.…”
mentioning
confidence: 99%